A Strategic Leadership Model for Teacher Evaluation Using Walkthroughs for Student Engagement at International Schools in Thailand - McGrath, John J; Laksana, Sangob (Scholar: Human Sciences, 2018)
This study used a multi-method approach to develop a model that changed the focus of teacher evaluation by using walkthroughs to guide teacher evaluation in order to increase student engagement utilizing a strategic leadership model. The objectives were (1) to explore the current practices in teacher evaluation, walkthroughs, and student engagement, (2) to determine the current practices of teacher evaluation, walkthroughs and student engagement at international schools in Thailand, (3) to develop the proposed strategic leadership model in teacher evaluation using walkthroughs to increase student engagement, and, (4) to implement the proposed strategic leadership model in teacher evaluation using walkthrough to increase student engagement in an international school in Bangkok. Current practices regarding teacher evaluation were established by using a content analysis-based questionnaire sampling schools registered with the International Schools Association of Thailand. The results of the questionnaire and the focus group interviews conducted, pointed to a major problem with teacher evaluation and its implementation. Current models of teacher evaluation and the leadership behind them were not effective. A new strategic leadership model was developed to use walkthroughs to improve student engagement. The model was implemented at a family of international schools in Bangkok over a six-month period. Walkthroughs gauging student engagement in areas of curriculum, instruction, environment and learning were conducted at the beginning and end of the trial period. A paired sample t-test was used to measure for statistical significance. In each of the four areas the findings were significant thereby validating the strategic leadership model and its application.